Hip Pain in an athlete - Covey, C. J.; Knobloch, A. C.; Kim, A. R. (Current Sports Medicine Reports, 2023)
Hip pain is a common complaint in sports, and narrowing the differential diagnosis can be difficult. Many etiologies are secondary to overuse and respond well to nonsurgical treatment. The increased use of point-of-care ultrasound has helped provide timely and accurate diagnoses and some guided treatments. The hip is in close proximity to the abdomen and pelvis, and clinicians should be familiar with nonmusculoskeletal pain generators. This article is a comprehensive review of hip pain etiologies in athletes.